Vocational training and European standardisation of qualifications: the case of aircraft maintenance - Haas, Joachim [Verfasser]; Ourtau, Maurice [Verfasser] (My University, 2009)
"Initiatives to standardise the conditions for practising certain regulated activities are being taken at European level, particularly in light of the free movement of people and the recognition of qualifications in Member States. This paper looks at the introduction of European licences for aircraft maintenance engineers. It follows an in-depth analysis of the process for the construction and application of these standards, and is an attempt to define the real motivation behind these special initiatives. It reports on how Community provisions which, in many respects, conflict with national structural characteristics in the area of qualification construction and management, are being transposed." (Autorenreferat, BIBB-Doku)
Keywords: S 6.4.2.1 Verkehrsberufe (inkl. Nachrichtenverkehr); S 2.2.5 Standards in der beruflichen Bildung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.1 Deutschland; I 2.2.1 Westeuropa; Luftverkehrsberuf; Bildungsstandards; Berufliche Qualifikation; Anerkennung; Fallstudie; Bundesrepublik Deutschland; Frankreich; Großbritannien